2020
DOI: 10.1101/2020.06.19.160879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-neutralization activity against SARS-CoV-2 is present in currently available intravenous immunoglobulins

Abstract: Background: There is a crucial need for effective therapies that are immediately available to counteract COVID-19 disease. Recently, ELISA binding cross-reactivity against components of human epidemic coronaviruses with currently available intravenous immunoglobulins (IVIG) Gamunex-C and Flebogamma DIF (5% and 10%) have been reported. In this study, the same products were tested for neutralization activity against SARS-CoV-2, SARS-CoV and MERS-CoV and their potential as an antiviral therapy. Methods: The neutr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
0
21
2
Order By: Relevance
“…With respect to the association with treatment duration, it has been shown that long‐term anti‐CD20 treatment is associated with the risk of hypogammaglobulinemia in neuromyelitis optica‐spectrum disorder 20 . A protracted treatment may impact on the protective, anti–SARS‐CoV‐2 humoral response 21 and on a pre‐existing humoral and cellular immune repertoire, recently described in unexposed individuals 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…With respect to the association with treatment duration, it has been shown that long‐term anti‐CD20 treatment is associated with the risk of hypogammaglobulinemia in neuromyelitis optica‐spectrum disorder 20 . A protracted treatment may impact on the protective, anti–SARS‐CoV‐2 humoral response 21 and on a pre‐existing humoral and cellular immune repertoire, recently described in unexposed individuals 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane systematic review indicated uncertainty as to whether convalescent plasma reduces COVID-19 disease mortality, although noted that it may increase improvement in symptoms at 15–30 days post-infusion [ 28 ]. In our patient's case we may have provided additional passive neutralizing anti-SARS-CoV-2 IgG through his IVIG infusions [ 29 ]. We were able to confirm the presence in the patient's circulation of broad IgG binding activity against SARS-CoV-2 viral proteins at several timepoints after plasma transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…al. published the detection of cross-reactive [12] as well as crossneutralizing Abs in 5 of 6 tested IVIG lots (Flebogamma and Gamunex C) [13]. This is in contrast to an earlier study which tested 21 IVIG lots (9 Gamunex C, 10 Gammagard Liquid, 2 other) with a SARS-CoV-2-specific ELISA (RBD or spike protein) that was shown to correlate well with a neutralization test, and revealed the absence of cross-reactive antibodies [14], as well as the current study.…”
Section: Discussionmentioning
confidence: 99%
“…of[13]). As two experimentally robust studies have not found SARS-CoV-2 nAbs in IVIG lots produced from pre-pandemic plasma, currently available IVIGs cannot be expected to afford protection from SARS-CoV-2 infection.No SARS-CoV-2 neutralization by IVIGs11With increasing numbers of human infections, also in the plasma donor community, it is interesting to follow the development of antibodies against SARS-CoV-2 in plasma donations and, after the several months production cycle time between plasma donation and IVIG lot release, also in IVIG lots, a longitudinal study currently in progress.…”
mentioning
confidence: 99%